A Comparative Review of Toll-Like Receptor 4 Expression and Functionality in Different Animal Species - Vaure, Céline; Liu, Yuanqing (Frontiers in Immunology, 2014)
Toll-like receptors (TLRs) belong to the pattern recognition receptor (PRR) family, a key component of the innate immune system. TLRs detect invading pathogens and initiate an immediate immune response to them, followed by a long-lasting adaptive immune response. Activation of TLRs leads to the synthesis of pro-inflammatory cytokines and chemokines and the expression of co-stimulatory molecules. TLR4 specifically recognizes bacterial lipopolysaccharide (LPS), along with several other components of pathogens and endogenous molecules produced during abnormal situations, such as tissue damage. Evolution across species can lead to substantial diversity in the TLR4’s affinity and specificity to its ligands, the TLR4 gene and cellular expression patterns and tissue distribution. Consequently, TLR4 functions vary across different species. In recent years, the use of synthetic TLR agonists as adjuvants has emerged as a realistic therapeutic goal, notably for the development of vaccines against poorly immunogenic targets. Given that an adjuvanted vaccine must be assessed in pre-clinical animal models before being tested in humans, the extent to which an animal model represents and predicts the human condition is of particular importance. This review focuses on the current knowledge on the critical points of divergence between human and the mammalian species commonly used in vaccine research and development (non-human primate, mouse, rat, rabbit, swine and dog), in terms of molecular, cellular and functional properties of TLR4.